2002
DOI: 10.1017/s0014479702000418
|View full text |Cite
|
Sign up to set email alerts
|

On-Farm Comparison of Feeding Strategies Based on Forages for Small-Scale Dairy Production Systems in the Highlands of Central Mexico

Abstract: The on-farm evaluation of three feeding strategies for smallholder campesino dairy herds was undertaken in the highlands of Central Mexico with cooperating farmers: traditional, alternative and intermediate feeding strategies. All three incorporated grazing of cultivated pastures, but concentrate use was 4.0 and 7.0 kg per cow per day in the rainy and dry seasons respectively for the traditional feeding strategy, 3.3 for the alternative feeding strategy in both rainy and dry seasons and 5.0 and 9.0 kg per cow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0
6

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 5 publications
0
19
0
6
Order By: Relevance
“…Milk yields were on the upper range of yields in these small-scale dairy systems (Arriaga-Jordán et al 2002), and are higher than yields reported by Woodward et al (2006) from work in New Zealand with no concentrate supplementation; reporting no differences in yields between cows with restricted grazing and supplemented with 5 kg DM of either maize or pasture grass silage; which were significantly higher than the cows on restricted grazing but without silage supplementation. MY were also comparable to those reported by Morrison and Patterson (2007) who reported slightly higher yields for cows receiving supplementary maize silage compared with cows on a grass silage treatment, similar to the results observed in the work herein reported where cows on the MS treatment had MY 0.06 higher than for the MIX treatment, in which the inclusion of herbage from the third cut after 73 days regrowth of the annual ryegrass resulted in lower digestibility and intakes; with no difference between the MS and ARG treatments.…”
Section: Animal Variablesmentioning
confidence: 54%
“…Milk yields were on the upper range of yields in these small-scale dairy systems (Arriaga-Jordán et al 2002), and are higher than yields reported by Woodward et al (2006) from work in New Zealand with no concentrate supplementation; reporting no differences in yields between cows with restricted grazing and supplemented with 5 kg DM of either maize or pasture grass silage; which were significantly higher than the cows on restricted grazing but without silage supplementation. MY were also comparable to those reported by Morrison and Patterson (2007) who reported slightly higher yields for cows receiving supplementary maize silage compared with cows on a grass silage treatment, similar to the results observed in the work herein reported where cows on the MS treatment had MY 0.06 higher than for the MIX treatment, in which the inclusion of herbage from the third cut after 73 days regrowth of the annual ryegrass resulted in lower digestibility and intakes; with no difference between the MS and ARG treatments.…”
Section: Animal Variablesmentioning
confidence: 54%
“…They feed lactating cows during the dry season (November to June) on stacked maize straw fed in the barns, plus grazing of the harvested maize fields, to collect any weeds, fallen straw and the odd maize cob. Commercial concentrates (18% crude protein) are supplemented at a rate of 3 to 5 kg/cow/day in these farms, with some farmers offering much larger amounts (Arriaga-Jordán et al 2002). Farmers sometimes also prepare mixtures of broiler litter, ground maize grain, and wheat bran plus ground maize straw (at a proportion of 25:60:5:10) to supplement the basal maize straw for dry cows, heifers and bulls, instead of using the commercial concentrates.…”
Section: Methodsmentioning
confidence: 99%
“…Small-scale dairy farming, representing small farms and herds of less than 20 cows plus replacements, may be a rural development option for smallholder campesino farmers in the highlands of Central Mexico, comprising the region between 18°and 22°N at altitudes above 1500 m, given its capacity to generate daily incomes and provide employment opportunities for farming families, reducing poverty and the need to migrate to cities (Arriaga-Jordán et al, 2002).…”
Section: Introductionmentioning
confidence: 99%